Comparison of the affective responses to continuous training and high-intensity interval training protocols: application of the dual-mode model - Alicea, S. K.; Parrott, A. D.; Manos, T. M.; Kwon, Y. S. (The Journal of Strength and Conditioning Research, 2021)
High-intensity interval training (HIIT) is time-efficient and has physiological benefits similar to or greater than that of continuous training (CT); however, there are mixed results regarding how HIIT protocols influence affect. The purpose of this study was to compare acute affective responses between HIIT and CT protocols over time using the Dual-Mode Model (DMM) as a theoretical framework. Subjects included 12 healthy women (aged 19-28 years) who completed a HIIT protocol consisting of a 2-minute work interval (100% VO2max) followed by a 2-minute rest interval (~55% VO2max), and a CT protocol set at the workrate corresponding to their respiratory compensation point (RCP; ~80% VO2max). Protocols were matched for average intensity, total duration, and energy expenditure. After blood pressure, anthropometrics, body composition, and VO2max measurements were taken, responses were recorded for affect (Feeling Scale [FS]), arousal (Felt Arousal Scale [FAS]), and rate of perceived exertion (RPE) before each protocol, during the last 10 seconds of every 2 minutes during the protocol, and at time points 2, 5, and 10 minutes after the protocol. Heart rate was also monitored continuously, and exercise enjoyment was measured before and after exercise. A repeated-measures analysis of variance revealed no significant differences in affect between CT (M = 2.5, SD = 2.1) and HIIT (M = 2.6, SD = 2.1) protocols over the duration of the exercise. There were no significant differences in mean RPE between CT (M = 12.9, SD = 2.7) and HIIT (M = 13.0, SD = 1.9) protocols (t = 0.333, p = 0.745) or in enjoyment between CT (M = 2.3, SD = 1.1) and HIIT (M = 2.0, SD = 0.9) protocols (t = -0.288, p = 0.492). In addition, based on visual inspection, the general patterning of the mean FS and FAS values between HIIT and CT was similar within the circumplex model, supporting the DMM. In conclusion, a HIIT protocol at VO2max and 1:1 exercise:rest interval did not result in a different affect response, perceived exertion, or enjoyment level when compared with a CT protocol at RCP.